The S19 earthquake in Morelos: the operational experience of INEEL in the evaluation of structural risk - Jesús Salvador García-Carrera; Ulises Mena-Hernández; Francisco Javier Bermúdez-Alarcón (Instituto Nacional de Salud Pública, 2018)
The earthquake of September 19, 2017 in Mexico caused catastrophic damage in the state of Morelos to more than 23 thousand structures in almost all municipalities. After an earthquake, emergency actions in the area are of great importance to support society, rescue trapped people as well as to assess the structural condition of the structures, and in this way, mitigate the negative effects. Unfortunately, society is not prepared to contain major disasters, and it can be very difficult to face a major emergency without the right conditions. The earthquake of September 19, with magnitude 7.1 and epicenter less than 75 km away, caused an emergency never expected in the state of Morelos, because of the damage it produced, which put Morelos' emergency system to the test. In particular, researchers from the National Institute of Electricity and Clean Energies (INEEL) initiated inspection actions in the buildings of their own institute, and subsequently placed themselves under the orders of the Civil Protection office of the State of Morelos to carry out post-seismic inspections of government buildings, schools and, in general, the homes of Morelos. The main task was to decide if the buildings were able to be inhabited again, if they should be evicted for a detailed review or if they should be demolished due to their high risk of collapse. The support was not only oriented to the post-seismic evaluation of the buildings, but was the beginning of working days with the State authorities, which will result in the improvement of the emergency plans and, above all, in the update of the design standards.